Islamophobia and the law - Choudhury, Cyra Akila; Beydoun, Khaled A. (Cambridge University Press, 2020)
Introduction / Khaled A. Beydoun and Cyra Akila Choudhury -- The Citizen and the Terrorist / Leti Volpp -- Race, Civil Rights, and Immigration Law After September 11, 2001 : the Targeting of Arabs and Muslims / Susan Akram and Kevin Johnson -- Constructing Good Aliens and Good Citizens : Legitimizing the War on Terror(Ism) / Karen Engle -- A Rage Shared By Law : Post-September 11 Racial Violence As Crimes Of Passion / Muneer I. Ahmad -- The Lost Story of Iqbal / Shirin Sinnar -- "Muslim Bans" and the (Re)Making of Political Islamophobia / Khaled A. Beydoun -- "Islamic Law" in U.S. Courts : Judicial Jihad or Constitutional Imperative? / Faisal Kutty -- A Muslim Registry : A Look at Past Practices and What May Come Next / Abed A. Ayoub -- National Security's Broken Windows / Amna Akbar -- Muslim Radicalization in Prison : Responding with Sound Penal Policy or The Sound of Alarm? / SpearIt -- Property Lawfare : Historical Racism And Present Islamophobia In Anti-Mosque Activism / Cyra Akila Choudhury -- "Liberty and Death" / Karen Rhone -- The Gender of Islamophobia / Aziza Ahmed -- Coercive Assimilationism and Muslim Women's Identity Performance in the Workplace / Sahar F. Aziz -- Conclusion.